A Model of Vertical Oligopolistic Competition - Markus Reisinger; Monika Schnitzer (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
This paper develops a model of successive oligopolies with endogenous market entry, allowing for varying degrees of product differentiation and entry costs in both markets. Our analysis shows that the downstream conditions dominate the overall profitability of the two-tier structure while the upstream conditions mainly affect the distribution of profits. We compare the welfare effects of upstream versus downstream deregulation policies and show that the impact of deregulation may be overvalued when ignoring feedback effects from the other market. Furthermore, we analyze how different forms of vertical restraints influence the endogenous market structure and show when they are welfare enhancing.
urn:nbn:de:bvb:19-epub-3189-9
Keywords: L13; D43; L40; L50; 330; Deregulation; Free Entry; Price Competition; Product Differentiation; Successive Oligopolies; Two-Part Tariffs; Vertical Restraints; Oligopol; Wettbewerbsbeschränkung; Produktdifferenzierung; Markteintritt; Deregulierung; Wohlfahrtsanalyse; Theorie